International human rights in a nutshell - Buergenthal, Thomas; Shelton, Dinah; Stewart, David P.; e uthor (2017)
"[This book provides an]...overview of the international, regional and domestic human rights systems. Reviews recent developments in the field, including in the UN, European, OAS and African human rights systems and the adoption of new conventions such as those on forced disappearances and persons with disabilities. Includes chapters on the treatment of human rights treaties and norms within the U.S. legal system as well as on the role of non-governmental human rights organizations. Discover the history behind international human rights, including the institutional context from which they evolved."--
Historical antecedents of international human rights law -- The United Nations human rights system -- The European system for the protection of human rights -- The inter-American human rights system -- The African and other regional systems -- Incorporation and application of human rights in the United States -- Non-state actors.
Includes bibliographical references and index.
Keywords: International law and human rights; Human rights; Human rights; International law and human rights; Study guides; Study guides